2009
DOI: 10.1159/000228542
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Hypoxia-Inducible Factor-1 Alpha and Cardiovascular Disease in Hemodialysis Patients

Abstract: Background: Hemodialysis patients are prone to ischemic events potentially aggravated by hypoxia. The key player in adaptation to hypoxia is hypoxia-inducible factor-1 alpha (HIF-1α). Therefore, we investigated the association of HIF-1α polymorphisms with ischemia/hypoxia-related events in hemodialysis patients. Methods: Patients on maintenance hemodialysis were enrolled from 4 training hospitals in Korea. Seven single nucleotide polymorphisms (SNP) of HIF-1α were genotyped. The association of these SNP with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Single-nucleotide polymorphisms (SNP) frequencies were similar in the two cohorts and comparable with those reported in the general population ( Table 1) (16)(17)(18). The two cohorts were comparable except for a higher frequency of blacks in cohort 1 vs. 2 (21% vs. 0%).…”
Section: Snp Frequenciessupporting
confidence: 66%
See 2 more Smart Citations
“…Single-nucleotide polymorphisms (SNP) frequencies were similar in the two cohorts and comparable with those reported in the general population ( Table 1) (16)(17)(18). The two cohorts were comparable except for a higher frequency of blacks in cohort 1 vs. 2 (21% vs. 0%).…”
Section: Snp Frequenciessupporting
confidence: 66%
“…Genotyping was performed for SNPs chosen based on previous association studies, functional effects, allele frequency, and prevalence (16)(17)(18): VEGFA 2578A/C, VEGFA 1154A/G, both SNPs in the VEGF promoter, VEGFA 634C/G in the 5′ untranslated region, HIF1A 145C/T, HIF1A 1326C/T, and HIF1A 1744C/T in the 3′ untranslated region ( Table 6). Functioning alleles (major alleles) in HIF1A and loss-of-function alleles (minor alleles) in VEGFA were considered risk alleles.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we found only one functional SNP locus (rs2057482), which located in the 3′-UTR. Another SNP locus, rs2301113, was selected as previous studies reported [26, 27]. Genotyping was performed using Sequenom iPLEX genotyping system (Sequenom Inc, CA).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in hemodialysis patients, polymorphisms are associated with acute myocardial infarction and hypotension (Zheng et al 2009). It is also associated with susceptibility to systemic sclerosis, a disease characterized by vascular inflammation and angiopathy (Wipff et al 2009).…”
Section: Hif-1amentioning
confidence: 99%